Morphological Plasticity and Abundance Patterns of Arrhenia antarctica in the South Shetland Islands: Implications for Fungal Ecology in a Warming Antarctica - Fernando Augusto Bertazzo-Silva; Jair Putzke; João Lindolfo Meira; Marisa Terezinha Lopes Putzke; Carlos Ernesto Gonçalves Reynaud Schaefer (Diversity)
The formation and development of mushrooms depend on suitable conditions of humidity, substrate, and temperature. These environmental factors are directly influenced by ongoing climate change, which may alter fungal growth patterns, distribution, and morphology. However, these attributes remain inadequately investigated in Antarctic mushrooms. In this study, we examined 334 basidiomes of Arrhenia antarctica, discovered on Livingston Island in 2023. The morphological characteristics of these basidiomes were analyzed to explore how recent variations may be linked to and explained by climatic changes. Comparing the original description from over 60 years ago with the recent literature on the subject, we observed a larger pileus diameter (47.3% of basidiomes with diameters exceeding 23 mm, up to 75 mm) than previously documented (reported as up to 23 mm). Additionally, there were changes in pileus morphology, with not all of them exhibiting an umbilicate form, contrary to the references. We propose that these morphological variations may be attributed to climatic changes. The basidiomata were also found in association with pure Antarctic grass banks, prompting the question of whether Arrhenia antarctica is indeed a moss parasite. The information presented in this study aims to support ongoing research on the taxonomy and diversity of Agaricales fungi in Antarctica.